2023
DOI: 10.3390/healthcare11060821
|View full text |Cite
|
Sign up to set email alerts
|

A Semantic Cognition Contribution to Mood and Anxiety Disorder Pathophysiology

Abstract: Over the last two decades, the functional role of the bilateral anterior temporal lobes (bATLs) has been receiving more attention. They have been associated with semantics and social concept processing, and are regarded as a core region for depression. In the past, the role of the ATL has often been overlooked in semantic models based on functional magnetic resonance imaging (fMRI) due to geometric distortions in the BOLD signal. However, previous work has unequivocally associated the bATLs with these higher-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…The region’s prominent role in self-blame has been pinpointed by studies showing the aberrant connectivity of this area with SCSR during guilt processing in MDD patients (Lythe et al, 2015; Green et al, 2012). By reporting sATL’s associations with both self-blaming behaviour and trait anxiety, our study underlines the key role it plays in the studied circuitry, implicating that the differential functional interactions of this region with the fronto-limbic emotional networks could underlie the prevalence of maladaptive forms of guilt observed across both mood and anxiety disorders (Kim et al, 2011; Candea and Szentagotai-Tătar, 2018; Green et al, 2012; González-García and Visser, 2023). The stronger interconnected left sATL in individuals with increased self-blame and trait-anxiety might reflect the tendency to ruminate over related negative social situations, which would require the sATL to access the related social-semantic information.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The region’s prominent role in self-blame has been pinpointed by studies showing the aberrant connectivity of this area with SCSR during guilt processing in MDD patients (Lythe et al, 2015; Green et al, 2012). By reporting sATL’s associations with both self-blaming behaviour and trait anxiety, our study underlines the key role it plays in the studied circuitry, implicating that the differential functional interactions of this region with the fronto-limbic emotional networks could underlie the prevalence of maladaptive forms of guilt observed across both mood and anxiety disorders (Kim et al, 2011; Candea and Szentagotai-Tătar, 2018; Green et al, 2012; González-García and Visser, 2023). The stronger interconnected left sATL in individuals with increased self-blame and trait-anxiety might reflect the tendency to ruminate over related negative social situations, which would require the sATL to access the related social-semantic information.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, Eslinger et al (2021) draws special attention to the right superior anterior temporal lobe (sATL) given that the connectivity between this region and SCSR during guilt processing is altered in the major depressive disorder (MDD) patients and has the ability to predict illness recurrence (Green et al, 2012; Lythe et al, 2015). With sATL suggested to be involved in accessing the conceptual representations of social meaning, and the activation of fronto-subcortical areas reflecting the affective dimension of guilt, it has been proposed that aberrant interactions between semantic and emotional networks might underlie the prevalence of maladaptive guilt across mood and anxiety disorders (Green et al, 2012; González-García and Visser, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the roles of the amygdala and hippocampus in fear and anxiety 20,21 , and developments in amygdala and hippocampal segmentation techniques (Saygin et al, 2017), there have been increasing reports of subfield volume alterations in anxiety-related disorders 22 . Reviews of the hippocampal subfields literature suggest that individuals with MDD have smaller volumes of the CA3/4 and larger volume of the hippocampus–amygdala transition area (HATA) compared to HCs 23 , while individuals with PTSD have smaller volumes of the CA1/3 and dentate gyrus (DG) compared to HCs (Ben-Zion et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, emerging evidence suggests that OCD involves additional brain circuits including the cerebellar, fronto-parietal, and fronto-limbic circuits (van den Heuvel et al, 2016). There has also been interest in investigating the hippocampal formation and amygdala in OCD, given the established roles of these brain structures in anxiety (Brühl et al, 2014; González-García & Visser, 2023; Shi et al, 2023) and fear conditioning (Cheng et al, 2003). Indeed, an fMRI study suggested that during fear conditioning, the hippocampus has reduced activation in patients with OCD compared to healthy controls (HCs) (Milad et al, 2013), and a meta-analysis indicated increased amygdala activation during emotional processing in patients with OCD versus HCs (Thorsen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%